Cladocolea spathiflora (Loranthaceae) a new species from Guerrero, Mexico - Galván-González, Luis Gil; Cerros-Tlatilpa, Rosa; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa (Phytotaxa, 2017)
Cladocolea spathiflora, a new species from Guerrero, Mexico, is described and illustrated. The new taxon is compared with C. pringlei and C. grahamii, species with similar characteristics; however, the flowers of C. spathiflora are associated to a spathaceous receptacle, while in the other two species the flowers are sessile on the axis of the inflorescence. An identification key and a distribution map of these taxa are included.